Subjective Cognitive Fatigue and Autonomic Abnormalities in Multiple Sclerosis Patients - Sander, Carina; Hildebrandt, Helmut; Schlake, Hans-Peter; Eling, Paul; Hanken, Katrin (Frontiers in Neurology, 2017)
Background: Cognitive fatigue and autonomic abnormalities are frequent symptoms in MS. Our model of MS-related fatigue assumes a shared neural network for cognitive fatigue and autonomic failures, i.e., aberrant vagus nerve activity induced by inflammatory processes. Therefore, they should occur in common. Objective: To explore the relationship between cognitive fatigue and autonomic symptoms in MS patients, using self-reported questionnaires. Methods: In 95 MS patients cognitive fatigue was assessed with the Fatigue Scale for Motor and Cognitive Functions (FSMC), and autonomic abnormalities with the Composite Autonomic Symptom Scale-31 (COMPASS-31). We used exploratory correlational analyses and hierarchical regression analysis, controlling for age, depressive mood, disease status and disease duration, to analyze the relation between autonomic abnormalities and cognitive fatigue. Results: The cognitive fatigue score strongly correlated with the COMPASS-31 score (r=0.47, p<0.001). Regression analysis revealed that a model including the COMPASS-31 domains pupillomotor, orthostatic intolerance and bladder best predict the level of cognitive fatigue (R=0.69, p<0.001) after forcing the covariates into the model. Conclusion: In MS patients cognitive fatigue and autonomic dysfunction share a large proportion of common variance. This supports our model assuming that fatigue might be explained at least partially by inflammation-induced vagus nerve activity.